Bioanalysis Young Investigator: Dajana Vuckovic. (May 2012) - Vuckovic, Dajana; Pawliszyn, Janusz
Supervisor's supporting comments Dajana currently has 21 peer-reviewed articles published or accepted for publication in top analytical chemistry journals including Analytical Chemistry and Angewandte Chemie International Edition . She has co-authored eight book chapters, and made 22 presentations at international conferences such as Pittcon and ASMS conferences. Dajana's commitment to excellence is also illustrated by the awards she has won to date, including a Postdoctoral Fellow Award offered by the Natural Science and Engineering Research Council of Canada (2010–2012) and the Douglas E Ryan Analytical Chemistry Student Award of the Canadian Society for Chemistry (2010). During her PhD in my group, Dajana excelled in very diverse areas of interest including the development of targeted LC–MS assays for drugs and metabolites, application of in vivo solid-phase microextraction (SPME) in mice and LC–MS metabolomics for the first time, and evaluation of a high-throughput 96-well plate automated SPME system. Since her graduation from my group she has further extended her bioanalytical expertise to proteomics. I think Dajana's excellent research productivity, accomplishments to date, willingness to address complex bioanalytical challenges and extensive expertise in both small molecule and protein bioanalysis make her an excellent candidate for the Bioanalysis Young Investigator Award.